Structural and concepcional changes related to the University of debrecen and its sport organizations between the period 2000–2013 - Lenténé Puskás, Andrea (Acta Agraria Debreceniensis, 2014)
The strategic and conceptional approach to sport has brought substantial changes in the sporting life of University of Debrecen during the period between 2005–2013. The restructualisation process aiming at the development of university sport as well as the measures related to creating a more transparent financing system demonstrates elements of improvement in comparison to the period prior to the Bologna process. The Sport Concept of the university operates the different areas of sport within a transparent, planed and complex structural framework in accordance with the principles outlined in both the National Sports Strategy (2007) and the legal regulations specified by the Sports Law and its modification (2004, 2011). The conceptional changes of sport at the University of Debrecen followed the main objectives and guidelines of the European Commission that lays a great emphasis on issues such as the integration of athletes into higher education allowing maintenance of parallel educational and athletic carriers for athletes.